Targeting the Endothelium to Achieve Cardioprotection - Herrera-Zelada, Nicolas; Zuñiga-Cuevas, Ursula; Ramirez-Reyes, Andres; Lavandero, Sergio; Riquelme, Jaime A. (Frontiers in Pharmacology, 2021)
Despite considerable improvements in the treatment of myocardial infarction, it is still a highly prevalent disease worldwide. Novel therapeutic strategies to limit infarct size are required to protect myocardial function and thus, avoid the progression to heart failure. Cardioprotection is a research topic with significant achievements in the context of basic science. However, translation of the beneficial effects of protective approaches from bench to bedside has proven difficult. Therefore, there is still an unmet need to study new avenues leading to protecting the myocardium against infarction. In line with this, the endothelium is an essential component of the cardiovascular system with multiple therapeutic targets with cardioprotective potential. Endothelial cells are the most abundant non-myocyte cell type in the heart and are key players in cardiovascular physiology and pathophysiology. These cells can regulate vascular tone, angiogenesis, hemostasis, and inflammation. Accordingly, endothelial dysfunction plays a fundamental role in cardiovascular diseases, which may ultimately lead to myocardial infarction. The endothelium is of paramount importance to protect the myocardium from ischemia/reperfusion injury via conditioning strategies or cardioprotective drugs. This review will provide updated information on the most promising therapeutic agents and protective approaches targeting endothelial cells in the context of myocardial infarction.